Intimate partner violence in pregnancy: Communicate better to unveil the problema. - Moreira, Rosa Maria Santos (2016)
Describe the prevalence of IPV during pregnancy in the Central Region of Portugal. Reflect on the need to improve the effectiveness of communication between nurse or midwife and pregnant woman or couple, for easier identification of violence exposure during pregnancy.